The Impact of AI-Generated NFT Art on the Global Art Market: Trends and Perspectives - Terekhova, Anastasiia (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
This study measures the impact of AI generated Non-fungible token art on global art market particularly in respect of sales volume, market value and the relationship in buyer behavior over time from 2020 - 2024. The research uses data from top Non-fungible token platforms, cryptocurrency market variables, and global economic indicators obtained from IMF and World Bank to analyze with multiple linear regression and binary logistic regression models. The findings suggest that AI generated Non-fungible token contributes to the growth of the digital art sales as sales volume increases and market value is increased. The results furthermore show that there’s a change in demographics of end-buyers when it comes to AI generated Non-fungible token as the investors are younger and tech savvy crowd consider crypto as an investment option. Such dynamics as social media engagement and cryptocurrency market dynamics become some factors that influence the market trends. From these analyses and for the art industry, it presents valuable insight as to how AI and blockchain technology could transform itself and how artists, investors and policymakers alike should arrange themselves.